2012
DOI: 10.3389/fphar.2012.00107
|View full text |Cite
|
Sign up to set email alerts
|

KCa2 and KCa3 Channels in Learning and Memory Processes, and Neurodegeneration

Abstract: Calcium-activated potassium (KCa) channels are present throughout the central nervous system as well as many peripheral tissues. Activation of KCa channels contribute to maintenance of the neuronal membrane potential and was shown to underlie the afterhyperpolarization (AHP) that regulates action potential firing and limits the firing frequency of repetitive action potentials. Different subtypes of KCa channels were anticipated on the basis of their physiological and pharmacological profiles, and cloning revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 151 publications
(224 reference statements)
1
32
0
Order By: Relevance
“…Physiologically, CaMKIIα regulates calcium-calmodulin - known to inhibit small ion conductance channels - in LTP (Grunnet et al, 2010; Mpari et al, 2010; Kuiper et al, 2012; Stackmam et al, 2008). Together, CaMKIIα, and these small channels occupy postsynaptic densities in the hippocampus (González et al, 2012; Trimmer, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Physiologically, CaMKIIα regulates calcium-calmodulin - known to inhibit small ion conductance channels - in LTP (Grunnet et al, 2010; Mpari et al, 2010; Kuiper et al, 2012; Stackmam et al, 2008). Together, CaMKIIα, and these small channels occupy postsynaptic densities in the hippocampus (González et al, 2012; Trimmer, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…As such, it was suggested that in primary cortical neurons, TNF-α induces K(Ca)2.2 channel activation, resulting in neurons that are more resistant to excitotoxic cell death by preventing intracellular calcium levels to become pathologically high [129,205]. In the past years it has been shown that K(Ca)2 channels may also be involved in mechanisms contributing to the plasticity of the hippocampal CA1 neurons and in learning and memory [206,207]. Fischer et al (2014) showed that TNFR2-mediated activation of the PI3K-PKB/Akt pathway in primary astrocytes induces the expression of different neuroprotective genes, including the gene that encodes leukemia inhibitory factor (LIF) [208].…”
Section: Tnfr2-possible Downstream Targets In Neurodegenerationmentioning
confidence: 99%
“…[1][2][3][4] The SK channel proteins SK1, SK2, and SK3 are encoded by KCNN1, KCNN2, and KCNN3 genes, respectively. 5 SK channels are characterized by their small single-channel conductance, activation by submicromolar [Ca 2+ ] i , voltage insensitivity, and selective blockade by the bee venom toxin apamin.…”
Section: Introductionmentioning
confidence: 99%